Enhancing pro-environmentalism of St. Theresa's College, Quezon City using green chemistry experiments - RAUL ENRICO, BERNARDO (Archīum Ateneo, 2015)
This study used green chemistry experiments as means of enhancing the pro-environmentalism St. Theresa's College, QC. The respondents answered three environmental surveys and one green chemistry survey to measure their attitudes, motivation, and values to